ECNutritive vegetables for healthy life - Koley, T. K.; Singh, B. K.; Singh, B. (Indian Horticulture, 2019)
Vegetables are diversified sources for various nutritional compounds which plays crucial role in maintaining of human health. Beside basic nutritional compounds like vitamins and minerals, they are richer sources for varied number of secondary metabolites which helps in maintaining the good health, prevent and/or reduce the risk of various life style diseases like cancer, cardiovascular diseases, diabetes, eye health etc. Indian Institute of Vegetable Research being premier research institute in vegetables research in NARS, take frontier role in nutritional research and identified many genotypes of vegetables, rich in bioactive compounds.